(untitled) (Journal on studies and research of academic knowledge, 2021)
This study presents the main characteristics found in the meanings of Paĩ Tavyterã Guaraní’s sacred names (Tupãéry) and medicinal plants (Pohã Ñana). The analyzed data come from elicitation, audiovisual recordings of qualitative interviews and natural conversations, as well as fieldwork ethographic notes from 1978 until 2021. The result of this analyses of the composition of names for both types of names shows that the designations for Tupãéry and Pohã Ñana come from the characteristics reflected upon the named person or plant.